A comparison of the relative friction and wear responses of PTFE and a PTFE-based composite when tested using three different types of sliding wear machines. (October 2015) - Mazza, Luigi; Trivella, Andrea; Grassi, Roberto; Malucelli, Giulio
Abstract: In this work, the tribological behavior of a commercially available polytetrafluoroethylene-based composite material filled with polyimide microparticles has been thoroughly investigated using different approaches. Specifically, two standard tribological tests, i.e., pin-on-disc and thrust washer measurements, have been compared with sliding tests performed on real components using a specially designed lab bench. The obtained results demonstrated that, despite the different testing methods (continuous rotation vs. reciprocating linear movement for the pin-on-disc/thrust washer and sliding tests, respectively), the different techniques provide highly comparable data within the adopted experimental conditions and can be successfully combined to assess the overall tribological features of this PTFE-based polymer composite.